Kiai dan Blater: Antara Kesalehan dan Kekerasan dalam Dinamika Politik Lokal di Madura - Sila, Muhammad Adlin (Studia Islamika, 2019)
Yanwar Pribadi. 2018. Islam, State and Society: Local Politics in Madura. New York: RoutledgeThis book talks about the relationship between Islam, state and society in Indonesia with a focal point on local politics in Madura. Specifically, this book tries to explain factors that have shaped the development of contemporary Islam and politics in Madura. One of the main arguments of this book is that local elite figures play greater roles than formal leaders such as village heads or regents in mobilizing communities in Madura. By focusing on both kiai and blater, this book examines the forms of the relationship between Islam and politics on one hand, and between piety and violence on the other. Anthropologically speaking, in order to produce a richer discussion, kiai and blater must be seen as social actors and not as a mere structure in their role of the construction of Islam and political formation in contemporary Indonesia.